2007
DOI: 10.1016/j.ejcts.2007.01.042
|View full text |Cite|
|
Sign up to set email alerts
|

Open-heart surgery in patients with liver cirrhosis

Abstract: Background: This retrospective study was designed to examine morbidity and mortality rates and to find predictors of outcome in patients with liver cirrhosis (LC) undergoing open-heart surgery. Methods: Between May 1996 and June 2005, 24 patients with LC underwent an open-heart surgery in our institution. Results: There were 14 females and 10 males. Their age ranged from 36 to 72 (average 53 AE 13) years. Seventeen cases were classified as having Child-Pugh class A cirrhosis, six as having class B cirrhosis, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 22 publications
(28 reference statements)
1
18
0
Order By: Relevance
“…An and colleagues reported that 25% of patients required re-exploration for mediastinal bleeding. 4 In our study, 33% of patients needed re-exploration for bleeding. The rate was much higher than in noncirrhosis patients and much more packed red blood cells, fresh frozen plasma, and platelets were needed.…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations
“…An and colleagues reported that 25% of patients required re-exploration for mediastinal bleeding. 4 In our study, 33% of patients needed re-exploration for bleeding. The rate was much higher than in noncirrhosis patients and much more packed red blood cells, fresh frozen plasma, and platelets were needed.…”
Section: Resultsmentioning
confidence: 96%
“…3 An and colleagues reported that the postoperative mortality of patients with Child class A, B, and C were 6%, 67%, and 100%, respectively. 4 Lin and colleagues reported that the overall mortality of liver cirrhosis patients was only 6%, and there were no deaths among Child B and C patients. They concluded that patients with mild and even advanced liver cirrhosis can tolerate open heart surgery.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…[11][12][13][14][15] The life expectancy of patients with cirrhosis is 40% of that of the general population. 16 The standardized mortality ratio for patients with cirrhosis for all causes of death combined is increased by 12-fold, with a relative 1-year survival rate of 67%.…”
Section: Discussionmentioning
confidence: 99%